Changes in the Nothern Border of the Home Range of the Dice Snake, Natrix tessellata (Reptilia, Colubridae), in the Dnipro Basin (Ukraine) - Nekrasova, O.D.; Gavris, G.G.; Kuybida, V.V. (Вестник зоологии, 2013)
A new distribution boundary of the dice snake, Natrix tessellate (Laurenti, 1768), in Ukraine has been established. The northern edge currently lies within the valley of the middle course of the Dnipro River: Trakhtemyriv Peninsula, Cherkasy Region on the right side (49°59' N, 31°25' Е); on the left side in Kyiv Region within Pereyaslav-Khmelnytsky District: at a fishermen’s station (50°02' N, 31°17' Е), yacht club (Kurinoye Estuary 50°02' N, 31°29' E); Lubny, Poltava Region (49°58' N, 33°01' Е). These points are located 70–80 km northwards from the previous boundary of the species home range. The level of Natrix tessellate population polymorphism in the North of Cherkasy Region is high; more than 40 % of specimens are dark-colored.